Dominasi Gender Terbalik dalam Komunikasi Rumah Tangga: Perspektif Dominasi Sosial Realitas ‘Suami Takut Istri’ - Karmanto Karmanto; Kelly Ayu Anggraeni; Muhammad Faqih Rusyda; Sa’diyah El Adawiyah; Tria Patrianti (SENTRI: Jurnal Riset Ilmiah, 2026)
The household reality commonly referred to as “husbands fearing their wives” in Indonesia reflects a shift in domestic power structures and reveals a form of reversed gender dominance. Within a society deeply rooted in patriarchal values, this shift indicates that household communication functions not merely as a medium for message exchange, but also as a space for negotiation and symbolic contestation between male and female roles. This study aims to conceptually examine the mechanisms of reversed gender dominance in marital communication by employing Social Dominance Theory as the main theoretical framework. The research uses a literature review method, analyzing various academic sources, including scholarly journals, books, and previous studies, that discuss issues of gender communication, power relations, and spousal dynamics within the Indonesian cultural context. The findings suggest that gender dominance within households is relational and dynamic, influenced by social, economic, cultural, and communicative factors between partners. The “husband fearing his wife” phenomenon should not merely be understood as a cultural form of humor, but as a reflection of the transformation of values and power structures in modern society. Through the lens of Social Dominance Theory, this dynamic can be interpreted as a communicative adaptation to social change and the growing awareness of gender equality within contemporary Indonesian families